ANARKISME EPISTEMOLOGIS PAUL KARL FEYERABEND SEBAGAI KRITIK ATAS OBJEKTIVISME ILMU PENGETAHUAN MODERN - za'im Kholilatul Ummi (JURNAL PUSAKA, 2019)
Abstract This paper discusses the thoughts of Paul Karl Feyerabend who criticized science which at the time was equated with religion. That everyone is required to believe and have the same way of thinking. Feyerabend then initiated the theory of epistemological anarchism as a form of his criticism of the position of science. The anarchism of knowledge carried by Feyerabend is a form of criticism of the establishment of a method in science, he called against method (anti-method) and criticism of its practice or function and position of science in society is called against science (anti-science). In his thinking, there are two things proposed by Feyerabend as his principle, namely the proliferation theory and the principle of anything goes. Feyerabend's thoughts in this matter are outlined in his book which is published under the title Against Method. Through the principles in Feyerabend's epistemological anarchism theory, it can be understood that the implication that comes from it is the pluralism of methods. Given Feyerabend anti against one method that is considered superior.Key Words: Paul Feyerabend, Criticism, Epistemological Anarchism, Pluralism.